Effectiveness And Safety of Shorter Treatment Regimen Containing Bedaquiline in Patients with Multidrug-Resistant Tuberculosis - Putra, Oki N. (Universitas Padjadjaran, Indonesia, 2024)
Bedaquiline have been included in the shorter treatment regimen (STR) to treat patients with multidrug-resistant tuberculosis (MDR-TB). The aim of this study is to evaluate the effectiveness and safety of STR containing bedaquiline. Data were collected retrospectively from medical records of MDR-TB patients receiving STR between January 2020 and December 2021. Sputum culture was evaluated at six months (24 weeks) and the end of treatment. Measurement of renal and liver function test, serum electrolytes, and uric acid were evaluated to assess safety during six months of treatment. Treatment failure, death, and loss to follow-up were also recorded during the study period. Thirty eligible MDR-TB met the inclusion criteria. Twenty-five of them had a positive culture at baseline. After treatment completion, 96.0% patients experienced sputum culture conversion. A significant decrease in potassium and calcium serum levels was observed at three months of treatment. Cases of treatment failure and loss to follow-up were 3.3% and 6.6%, respectively. MDR-TB patients receiving STR containing bedaquiline demonstrated favorable sputum conversion with tolerable safety profile